Other applications of plant extracts in dentistry - Martins, Christine Men; Quintino Trizzi, Juliana [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Piazza, Bruno; Matheus, Henrique Rinaldi [UNESP]; Dezan Junior, Eloi [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
Alternative treatments or coadjutants should be studied and proposed, especially considering the global trend and boosting the world health organization towards natural substances and medicinal plants, regarding their advantages as a function of its diversity, flexibility, accessibility, availability and wide acceptance. In this context, current researches have evaluated the effectiveness of natural substances, medicinal plants, phytoterapy and homeopathics: (1) as storage media for avulsed teeth or root surface treatment before teeth replantation; (2) as coadjutant to improve osteointegration and reduce peri-implantitis in dental implants; (3) as an alternative for anesthetic agents; (4) within treatment for bone remodeling during orthodontic movement or rapid maxillary expansion; (5) as hemostatic agents; and (6) as dental plaque disclosing agents. This chapter will discuss several studies regarding to all these related topics.
Keywords: Dental Implants; Hemostatic Agents; Phytotherapy; Plant Extracts; Tooth Avulsion